Gauge groups from brane-anti-brane systems at angles - Vancea, IV (World Scientific Publ Co Pte Ltd, 2001)
We discuss a system formed by two pairs of brane-anti-brane that form an arbitrary angle in a plane. We identify the gauge groups from this system which presumably could be used to construct gauge theories.